Unsur-unsur dasar pendidikan Islam - Ain, Failla Aylana (Maliki Interdisciplinary Journal, 2025)
Education is a means of developing one's abilities to become a human being who has three basic abilities, namely: intelligence, humanity, and religion. Therefore, education is a means of change to change ourselves and the society around us. Simply put, education is often interpreted as a human drive to develop individual personalities in accordance with the values of a society or culture. The process of religious education includes several elements such as students, teachers, educational interactions, educational goals, educational content, tools and methods, and the educational environment. The first educational component of a student represents an important part of the educational process and helps determine the success of the process. Second, educators have the responsibility to provide guidance and support regarding the physical and mental development of their students. Third, educational interaction, namely the existence of two-way communication between students and teachers towards educational goals. Fourth, Islamic teaching materials given to students are in accordance with the educational goals to be achieved. The goal is to form a noble moral concept, which is in line with the natural creation of humans. Fifth, educational tools refer to things that help achieve educational goals. Sixth, the environment plays an important role in Islamic education by influencing the development and formation of student character..